ROLE OF MULTI-STRAIN PROBIOTICS IN PRESENTATION OF SEVERITY AND FREQUENCY OF ALLERGIC RHINITIS (The Research of Medical Science Review, 2024)
Background: Allergic rhinitis (AR) is a common inflammatory condition characterized by nasal congestion, sneezing, and itching, driven by immune dysregulation. While conventional treatments provide symptom relief, they often fail to address underlying immunological imbalances. Objective: This study aimed to evaluate the efficacy of multi-strain probiotics in improving AR symptoms, quality of life, and immunological markers compared to a placebo. Methods: A randomized, double-blind, placebo-controlled trial was conducted at the Department of Pediatrics, Abbasi Shaheed Hospital during January 2024 to June 2024 with 135 patients diagnosed with AR. Participants received either a multi-strain probiotic formulation or placebo daily for 12 weeks. Outcomes included Total Nasal Symptom Score (TNSS), Rhinoconjunctivitis Quality of Life Questionnaire (RQLQ) scores, serum IgE levels, and eosinophil counts. Data were analyzed using intention-to-treat principles. Results: The probiotic group demonstrated a significant reduction in TNSS (46.9%) compared to the placebo group (16.3%), along with greater improvements in RQLQ scores (mean difference: 1.2, p < 0.001). Serum IgE levels and eosinophil counts decreased significantly in the probiotic group, highlighting immunological benefits. Adverse events were mild and comparable between groups. Conclusion: Multi-strain probiotics effectively reduce AR symptoms, improve quality of life, and modulate immune markers, offering a safe and valuable adjunct to traditional AR management. Further research is recommended to explore long-term benefits and personalized applications.